The Relationship Between Physical And Mental Workload On Job Fatigue In Maxim Car Drivers In Kupang City In 2024 - Misam Selan, Arwadi; Umbu Roga, Anderias; Christiani Berek, Noorce; Ruliati, Luh Putu (Ann Publisher, 2024)
Transportation is a system consisting of certain facilities along with the flow and control system that allows people or goods to move from one place to another efficiently at any time to support human activities. Indonesia as a developing country certainly has a very rapid development of services in the fields of land, sea and air transportation. Transportation owned by the Indonesian Nation certainly has innovations from past to present in order to advance transportation services, one of which is an online provider company. Online transportation companies offer transportation services such as online motorcycle taxis, online taxis, delivery of goods, food delivery and so on, thus making this service in demand by many people. Likewise in Kupang City where there are several online transportation options, one of which is Maxim car transportation which has the advantage of being quite cheap. The high demand for Maxim online transportation in Kupang City has an impact on the fatigue experienced by online transportation drivers. One of them is also felt by Maxim Mobil drivers. Based on the researcher's initial survey of Maxim drivers in Kupang city, fatigue often occurs in Maxim Car drivers due to the increase in Maxim Car users in Kupang City. This type of research is quantitative using analytic survey method and cros sectional research design. The sample in this study amounted to 81 respondents from a total population of 430 drivers selected using accidental sampling method. The results showed that there was no significant relationship between physical load and work fatigue and there was a significant relationship between mental load and fatigue in maxim car drivers in Kupang City.